DMS: Delusional Misidentification Syndrome or Dead Moneyman and Sex Offender? A Case Report of Reverse Capgras Syndrome - Kim, Elizabeth; Murphy, Rachael; Driscoll, Maggie (Case Reports in Psychiatry, 2022)
Delusional misidentification syndromes (DMSs) are delusional phenomena where individuals believe that one has been altered or replaced. Here, we present the case of Ms. JS, who exemplifies one such DMS, Reverse Capgras Syndrome, which refers to the delusion that one has been replaced by an imposter. She endorsed psychosis and suicidality centered on her belief that she was in fact American financier and convicted sex offender Jeffrey Epstein. Her delusion was eventually resolved with medication management and therapy. In this report, we review Reverse Capgras Syndrome in the context of existing research on trauma-related pathology and the neural basis of self. We also demonstrate the success of resolving what was initially concerning for a fixed delusion with patient-centered medication management and therapy. This case is presented as a vital contribution to the literature to bring awareness to a rare disorder with a poorly understood etiology that had a favorable outcome. Here, it is suggested that DMS may arise due to disrupted functional connectivity between highly coordinated brain networks, as evidenced by its occurrence in both organic neural disease and, as in this patient, trauma-related psychopathology.